Genetic characterization of drug resistant clinical isolates of Mycobacterium tuberculosis circulating within the Copperbelt province and Northern regions of Zambia. - Chisompola, Namaunga Kasumu (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2019.